Gestão de Recursos Humanos no setor vitivinícola: um estudo comparativo Brasil Portugal - Maria de Lourdes Moreira Braga (2012)
The human resource management, while organizational practice and field of theoretical discussion, occupies a prominent place among the dimensions of interest academic and management. Trying to understand its peculiarities and nuances, this work presents a comparative study conducted on companies in the wine industry in Brazil and Portugal. Through qualitative-descriptive research carried out in ten portuguese companies as well as in five Brazilian companies the results obtained from semi-structured interviews and document analysis allowed to consider that the way the companies studied in the two countries coordinate their Managements of Human Resources is very similar. The competitiveness of companies have in their managers and winemakers a central references, while the activity of human resources is restricted to a more technical field. The conclusions point to the evidence related common features in the companies studied in the two countries, namely, family background, which shows a model of organization and management with the presence of traits and values in business that extend to relationships with employees, even with requirements of behaviors consistent with the ideals advocated by the family. Aspects such as loyalty and trust have been identified in the interviews as elements that permeate the daily life of these organizations.